Recent developments on morphometric analysis of karst caves - Leonardo Piccini (Acta Carsologica, 2011)
Nowadays, the use of computers and the digital techniques for survey processing easily allows to carry out morphometric analysis of caves and karst systems. Morphometric indices have been proposed by many authors in order to describe the genetic features of some particular types of caves, suchas coastal ones, maze caves or isolated voids. Large cave systems can be analyzed throughthe reconstruction of a 3D model. The digital model can be used to evaluate the role of the structural setting or the evolution stages throughthe recognizing of particular levels where epi-phreatic passages are more developed. These levels are particularly significant when a lithological or structural control can be excluded. Some morphometric indices, obtained by the ratios of simple dimension parameters of caves, allow the statistical analysis of large databases, collected in the regional speleological inventories, in the attempt to recognize different geomorphic populations of caves. Further studies and a greater number of analysis could allow to use these morphometric indices to distinguishgenetic categories of caves and to get a useful instrument for the study of the evolution of karst areas.